Residual concentration of PAHs in seafood from Hormozgan province, Iran : human health risk assessment for urban population. - Mohebbi Nozar, Seyedeh Laili; Ismail, Wan Ruslan; Zakaria, Mohamad Pauzi (International Association of Computer Science and Information Technology Press, 2013)
This study is to determine the concentrations of sixteen poly aromatic hydrocarbons in eighteen pooled samples of fish, shrimp, crab and bivalve from markets of Hormozgan province, Iran. The poly aromatic hydrocarbon levels varied from 16 ± 8.4 to 28.18 ± 3.74 ng/g wet weight. The investigated samples were classified as minimally contaminated. Distribution patterns showed that PAHs with 4, 5 and 6 rings dominated, confirming the pyroge nic source of detected PAHs. Fish contributed more than other biota groups in transforming of PAHs to Hormozgan Province people. The average of B (a)P eq)values for the studied biota was 2.71 ± 2.28 ng/g that was greater than calculated local screen value. This finding was implemented in poor quality of studied biota and necessity for risk management.